Comparative Analysis of Perceptions Regarding the Hazards of E-Cigarette use Among Sports Science and Health Science Students - Wakhyu Saputra; Nur Inayah Ismaniar (Journal of Scientific Insights, 2026)
E-cigarette use is a growing trend among students and has attracted attention due to its health impacts. This behavior is influenced not only by individual factors but also by social factors, particularly peer groups, including social interactions, peer habits, and group solidarity. This study aimed to determine the relationship between social interactions, peer habits, and group solidarity with e-cigarette use among students at the Faculty of Sport and Health Sciences, Universitas Negeri Makassar (FIKK UNM). A quantitative study with an observational-analytical design and a cross-sectional approach was employed. A total of 330 respondents were obtained using the Slovin formula. Data were collected using a questionnaire and analyzed using the chi-square test in SPSS. The results showed that 199 respondents (60.3%) did not use e-cigarettes, while 131 (39.7%) did. Bivariate analysis revealed a significant relationship between social interaction and e-cigarette use (p = 0.001), peer habits and e-cigarette use (p = 0.001), and group solidarity and e-cigarette use (p = 0.001). Peers play a significant role in e-cigarette use among students through social interaction, imitation of peers' habits, and the drive to maintain group solidarity. Prevention efforts should therefore target not only individuals but also the broader student social environment. These findings are relevant to SDG 3 (Good Health and Well-being), as addressing e-cigarette use among young people is essential to ensuring healthy lives and promoting well-being for all ages.